Potencial efeito anticâncer da Lectina Canavalia brasiliensis (ConBr) - Dantas, Bruna Braga (2018)
Changes in the pattern of glycosylation during the carcinogenesis process have facilitated the recognition of cancer cells for diagnosis, determination of cancer progression and development of therapeutic strategies. Thus, lectins have shown promising results in anticancer studies by being able to recognize specific carbohydrates. Thus, this study evaluated the anticancer potential of Canavalia brasiliensis lectin (ConBr) and produced a ConBr-liposome formulation. For this purpose, the cell viability evaluation (MTT) in human myeloid leukemia chronic lines (K562 and K562-Lucena), acute monocytic leukemia (THP-1) and melanoma (SKAMEL) were also evaluated, and the effect on the lineage of murine melanoma (B16-F10), non-cancerous human lineage (HUVEC), and primary culture of peripheral human blood mononuclear cells (PBMC), the mechanism of cell death was further characterized by flow cytometry. It was demonstrated that in 24h incubation, ConBr induces cell death in the THP-1 line, with an IC 50 of 89.9 ± 1.4 µg.mL-1, and in the non-carcinogenic strain HUVEC, with an IC50 of 50.6 ± 1.3 µg.mL-1, this effect was also observed after 72 h of incubation in the K562 and PBMC lines, with IC50 of 34.5 ± 1.3 and 10.5 ± 1.2 µg.mL-1, respectively. This cytotoxic effect was confirmed by an increase in the sub-G1 fraction, indicating DNA damage. In the THP-1 and K562 leukemic lines, the sub-G1 increase was induced from 3 h incubation, with values of 30.2 ± 0.3 and 32.8 ± 4.7 %, respectively. After 24h of incubation, mitochondrial depolarization increased with 73.2 ± 03 % and 63.4 ± 5.9 %, respectively, for the THP-1 and K562 lineage, resulting in an increase in ROS, and when incubated with the antioxidant N-acetyl-cysteine (NAC), the effect of the lectin was inhibited. These characteristics corroborate with the activation of programmed cell death and it was shown that the lectin in the K562 strain increased the formation of acidic vesicle organelles (26.0 ± 3.7 %) and induced damages to the plasma membrane (11.5 ± 3,3 %), In the THP-1 strain, caused phosphatidylserine externalization (62.2 ± 3.2%), increased p53 expression (42.3 ± 10.6 %), increased cytochrome c intracytoplasmic expression (23.0 ± 2.9 %) and activated caspase 3 (30.7 ± 0.4 %). These effects depend on the structural integrity of the lectin, which was maintained inside a liposome composed of phosphatidylcholine with 10 mM DODAC, under the temperature range of 2 to 130 ° C, and at different pH (3.0, 7.4, 9.0). It was concluded that ConBr demonstrated a potential anti-leukemic effect, presenting selective cytotoxic action for THP-1 lineage with activation of intrinsic apoptosis, and induction of autophagy in the resistant leukemic strain, K562, being possible to maintain its quaternary structure under different temperature and pH.